Analisis Kelayakan Buku Tematik Kurikulum 2013 Tingkat Sekolah Dasar (Perspektif Pendidikan Karakter) - Di'amah Fitriyyah (ESTETIK : Jurnal Bahasa Indonesia, 2018)
The focus of this qualitative research is the feasibility analysis of 2013 curriculum thematic books at elementary school level character education perspective. This research through literature study describes, identifies, analyzes qualitatively about character education that appears in thematic books and their feasibility for teaching materials for elementary school age children. Character education in the thematic book title Obligations and My Rights published by the Ministry of Education and Culture, appeared 69 times. In sub-theme 1 appears 9 times, sub-theme 2 appears 15 times, subtema 3 appears 24 times, and in sub-theme 4 appears 21 times. Emerging character education is divided into 5 categories. Character education related to God, is related to oneself, related to fellow human beings, related to nationality, and related to the environment. The feasibility of thematic books in terms of character education is very feasible because character values appear as 69 times. This is also relevant to the structure of the 2013 curriculum which emphasizes meaningful learning. In the case of conveying character values when viewed in terms of children's cognitive development there are about 9 discussions that are not appropriate at the stage of concrete operational development. Keywords: Book Feasibility, Character Education